ANALISIS PENERAPAN METODE RAINWATER HARVESTING PADA KAWASAN PERUMAHAN G-LAND PADALARANG UNTUK MENJAGA KETERSEDIAAN AIR TANAH - Pratiwi, Vitta; Permana, Endang (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2017)
Increasing demand of housing facilities has an impact on the change of land function of an area that originally forest or garden turned into a residential area. Unbalanced water surface and ground surface are the effect of the unbalanced hydrologic cycle. Volume increased and runoff, infiltration capability and groundwater decreased levels are due to hydrological cycle imbalances. That is why water management is needed in order to create a balance of water resources. One way to realize the idea is to apply rainwater harvesting methods to a residential area that is a method of collecting rainwater that is stored in a storage tank for then the water that has been collected can be reused as an alternative source of clean water. The purpose of this research is to aims the potential of rainwater that can be harvested in G-Land Padalarang Housing area, so it can be used as a source of clean water as well as efforts to maintain groundwater availability and balance of hydrological cycle. The method is by using rational method. The data used are primary data and secondary data which then analyzed based on hydrologic and hydraulics analysis. From the analysis result, by applying rainwater harvesting method in G-Land Padalarang Housing area, the volume of water that can be harvested with rainfall 2,929 mm / year and the catchment area of 66 m2 is 173,983 liter / year and can save ground water usage of 52 % of total needs.